Recurrent ischemia following acute myocardial infarction in the elderly.: Unusual initial presentation of Takayasu’s arteritis - Murillo Pérez, Luis (2022)
We present the case of a 62-year-old male who presented with oppressive chest pain and was then diagnosed with acute myocardial infarction and received reperfusion treatment with primary angioplasty. In the evolution, he had a new episode of myocardial infarction, so complementary studies were carried out that led to the diagnosis of Takayasu’s arteritis. Unfortunately, he presented a torpid evolution despite the established management. The clinical presentation in patients older than 60 years is uncommon, so it is important to consider it within the differential diagnosis in patients with diffuse coronary disease and recurrent myocardial ischemia, due to the rapid progression and high morbidity and mortality despite successful revascularization strategies.